Reaching Effective Consensus : Monterrey and the Development Agenda - Page, John (World Bank, Washington, DC, 2012)
Recent international conferences have reflected a renewed interest in development. Among the most notable have been the 2001 Ministerial Conference of the World Trade Organization in Doha, Qatar, which launched the "development round" of talks on trade liberalization; the 2002 World Summit on Sustainable Development in Johannesburg, South Africa; and the 2002 International Conference on Financing for Development in Monterrey, Mexico, which resulted in the Monterrey Consensus on the international agenda for development. The Monterrey Consensus focuses on increasing international cooperation to reduce poverty in developing countries by: Improving policies and outcomes in these countries. Delivering more-and more effective-aid from donor countries. Improving market access for exports from developing to industrial countries. Advocates of the consensus see it as evidence of a stronger voice for developing countries in issues related to their development and of a renewed commitment by industrial countries to increase aid and market access. But critics claim that the Monterrey Consensus is little more than artifice-and that deep rifts between rich and poor countries prevent tangible progress.